Preparation of Biofertilizers from Banana Peels: Their Impact on Soil and Crop Enhancement - Nokuthula Khanyile; Ndumiso Dlamini; Absalom Masenya; Nothando Clementine Madlala; Sabelo Shezi (Agriculture)
Disposing of banana peels (BPs) as bio-organic waste is an environmental challenge. Rich in potassium, BPs are often discarded despite their agricultural value. Reports on the valorization of BP are increasing, but no review has focused on BP fertilizer preparation methods. This study aims to review and analyze these methods to guide researchers and agriculturists in optimizing BP utilization, promoting sustainable waste management, and effective agricultural practices. This review has uncovered significant findings. A composite of banana and orange peels emerged as the most favoured and widely used approach, closely followed by dried BPs. This study highlighted the substantial impact of fertilizer application methods such as top and basal dressing. Most of the results revealed that the peels significantly improved the growth parameters of various plants. However, for biochar, the plant height was insignificant between treatments, further emphasizing the importance of the application method used. Banana peels are a valuable resource for biofertilizer synthesis. The banana–orange peel composite exhibits outstanding fertilizer properties. More new studies should go beyond the seedling stage, especially to harvest. This would give more information on the performance and viability of BP fertilizers.